STATCOM modeling for mitigation of voltage fluctuations caused by electric arc furnaces - Agüero, Jorge Luis (2006)
Voltage fluctuations caused by rapid industrial load changes have been a major concern for both power companies and customers in the area of power quality. The fast response of the Static Compensator (STATCOM) makes it an efficient solution for improving power quality in distribution systems. This paper describes a model for a PWM-based STATCOM used in a distribution system for mitigation of voltage fluctuations produced by an Electric Arc Furnace (EAF). The analyzed system is modeled using MATLAB/Simulink Power System Blockset (PSB), including a complete STATCOM model with its power circuits and its control system. The complete model is validated by field test. Static and dynamic performance of STATCOM is evaluated and voltage fluctuation mitigation studies are performed and discussed. The voltage fluctuation mitigation is obtained by measurements and according to international standards.